PENERAPAN METODE QUANTUM HIJAIYAH DALAM MENINGKATKAN KEMAMPUAN BACA AL-QURAN KOMUNITAS MUALLAF DI KALIMANTAN BARAT - Samsul Hidayat (Jurnal Dakwah Tabligh, 2019)
This research is entitled: "Application of the Quantum Hijaiyah Method in Improving the Ability to Read the Koran of the Muslim Community in West Kalimantan”. The purpose of this study is to guide the convert community (muallaf) to be able to read the Qur'an properly and correctly, equipping them with the ability to practice one of the teachings of Islam, namely to read the holy verses of the Qur'an in order to increase the spirit of converts in practicing Islamic teachings.The object of this research is the Muslim convert community (muallaf) in Senyabang Village, Sanggau District and the Muslim Community in Menjalin Village, Menjalin District, Landak Regency. This qualitative research model targets the social community as an active part of the research process, in order to increase the effectiveness of the data collection and analysis process to produce a recommendation that is truly beneficial for the improvement of the quality of their social life. The community-based research approach is more suitable if it uses an action research model, as applied research that requires dynamic and clinical trials. The results of the study were in the form of application a method of learning the Qur'an in an easier time with the Quantum Hijaiyah method. The training and development participants showed an increase in the mastery of reading hijaiyah letters and verses of the Qur'an during 19 hours of effective learning starting from pre-test, training and post-test activities. Increasing the reading ability of participants is proven by the results of tests and testimonials or acknowledgment from each participant who acknowledges the changes and improvement in the quality of reading the verses of the Qur'an.